Numerical Analysis of Crack Initiation and Propagation in an Aluminium Sample - Różyło Patryk (Technical Transactions, 2018)
This paper reports an analysis of simulated crack propagation in an aluminium sample depending on the direction of external loads. The objective of the study was to perform a numerical analysis of crack propagation as well as to determine regions which are most susceptible to failure. The object of study was created from numerical analysis of material failure due to fibre separation using Abaqus 6.14. The modelling of crack propagation was performed using the numerical xFEM method for separating material fibres irrespective of the finite element mesh.